The Financial Analisis Efektifitas Pengelolaan Modal Kerja Dalam Meningkatkan Kinerja Keuangan Pada RSUD Bayu Asih Kabupaten Purwakarta - Lusiana Badriah; Widiya Avianti (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2023)
Management of working capital hospital operational costs is the need for operational, to improve financial performance effectively and efficiently in accordance with the Permendagri number 79 of 2018 concerning BLUD. The aim research is to determine the condition of working capital, to analyze the management of working capital with the financial performance of the hospital and to find out the turnover of working capital so that it is effective and efficient. Methodology uses a qualitative with a case study approach at Bayu Asih Hospital, Purwakarta. The research subjects of key respondents from the finance department and expert respondents, namely the vice director of general affairs and finance. The data analysis technique was triangulation of the results of observations, interviews, documentation of financial reports from 2017 to 2020 before the impact of the covid pandemic, classified based on themes and research findings and then analyzed using SWOT analysis. The results of research on working capital management in 2017 to 2020 are not fixed. Management of working capital to improve financial performance at BLUD Hospital pays attention to current assets and short-term liabilities so that it effectively and efficiently improves financial performance.